QUALITY OF LIFE AND SURGICAL TREATMENT IN WOMEN WITH GENITAL PROLAPSE (International conference on multidisciplinary science, 2025)
The use of an ultra-light polypropylene implant according to the developed method of its installation reliably improves the quality of life of patients in comparison with preoperative indicators and with the use of a lightweight implant and their own tissues. The use of an ultra-light implant increases the physical component of health by 32.0%, and the psychological component by 40.7%, which is significantly greater when using a lightweight (26.1% and 29.4%) and own tissues (14.4% and 19.3%) (p